132k views
4 votes
Inverse of y= x-6/x+5

1 Answer

3 votes

as you would already know, we start off to gettting any inverse of any expression by doing a quick switcheroo on the variables and then we solve for "y".


\bf y = \cfrac{x-6}{x+5}\implies \stackrel{\textit{quick switcheroo}}{x = \cfrac{y-6}{y+5}}\implies x(y+5)=y-6\implies xy+5x=y-6 \\\\\\ xy+5x+6=y\implies 5x+6=y-xy\implies 5x+6=\stackrel{\textit{common factor}}{y(1-x)} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill \cfrac{5x+6}{1-x}=\stackrel{f^(-1)(x)}{y}~\hfill

User Elley
by
5.8k points